Endoplasmic reticulum stress-related super enhancer promotes epithelial-mesenchymal transformation in hepatocellular carcinoma through CREB5 mediated activation of TNC - Anqi Wang; Sitong Yan; Jiatao Liu; Xiang Chen; Mengyao Hu; Xiao Du; Weijia Jiang; Zhipeng Pan; Lulu Fan; Guoping Sun (Cell Death and Disease)
Abstract Super-enhancers (SEs) are associated with key genes that control cellular state and cell identity. Endoplasmic reticulum stress (ERS) regulates epithelial-mesenchymal transformation (EMT). However, whether SEs are involved in ERS-related activation of EMT in hepatocellular carcinoma (HCC) is unknown. In this study, we identified 17 ERS-related SEs by comparing ERS-HCC cells with untreated control cells using ChIP-seq and RNA-seq. CRISPR-Cas9 and RT-qPCR identified CAMP responsive element binding protein 5 (CREB5) as a key target of ERS-related SE. Analyses of TCGA datasets and tissue arrays showed that CREB5 mRNA and protein expression levels were higher in liver cancer tissues than in paired normal tissues. In addition, overexpression of CREB5 was associated with poor prognosis and an aggressive phenotype in patients with HCC. We also found that activation of ERS enhanced the expression of CREB5, and upregulation of CREB5 significantly increased cell proliferation, migration, and invasion, and promoted EMT, but inhibited apoptosis. More importantly, ERS activation increased the expression of several EMT markers by modulating the expression of CREB5. Mechanistically, CREB5 upregulates the transcription of tenascin-C (TNC) by directly binding to its promoter region, thereby promoting EMT in liver cancer cells. In summary, our findings suggest that ERS activation promotes EMT in liver cancer cells via SE-mediated upregulation of the CREB5/TNC pathway. This result provides a new direction for uncovering how ERS regulates EMT and a foundation for preventing the progression of EMT in HCC.